OS GESTOS UTILIZADOS POR PROFESSORES AO ENSINAR GEOMETRIA - Castro, Laura Tiemme (2022)
There are different ways to represent a mathematical object, which can be through figurative, written, oral, mathematical representations and also through gestures. Gestures can represent the student's state of knowledge about a certain content from their inconsistencies with speech. In addition, we can see how the gestures produced by teachers influence student learning. The interest in the subject began in the meetings of the Group of Studies and Research in Geometry (GEPGEO), from the participation of the master's student, still in the graduation. In studies on the subject, we noticed that the production on the subject was focused on the gestures that students performed during an activity. In turn, there were few works on the gestures performed by teachers when teaching mathematics. With this, the interest in how teachers' gestures influence the learning process arose, but we believe that before that we should answer the question: what types of gestures do teachers use when teaching geometry? Therefore, the master's research has the general objective of identifying and categorizing the gestures used by teachers when teaching geometric concepts. This research is of a qualitative nature and as a collection instrument we used the recording of classes on geometry content from three Basic Education Mathematics and then we performed the classification of gestures according to McNeill (1992) and Edwards (2003). As a result of the research, we obtained that teachers mostly use Iconic-symbolic and Deictic gestures, that is, gestures that visually represent the mathematical content of speech and pointing gestures, respectively. It was also noticed that there is no significant difference in the amount of gestures used by elementary school and high school teachers.